Antibiotic Policy: An Essential, Time Demanded but Ignored Reality in Treating Infectious Diseases in Bangladesh (Bangladesh Journal of Medical Microbiology, 2016)
Abstract Not AvailableBangladesh J Med Microbiol 2008;2(2):1-2